Thermodynamic modeling of the PbX (X=S, Te) phase diagram using a five sub-lattice and two sub-lattice model. (September 2017) - Peters, M.C.; Doak, Jeff.W.; Zhang, W.-W.; Saal, J.E.; Olson, G.B.; Voorhees, P.W.
Abstract: Five-sublattice and two-sublattice models have been built to describe the PbX (X=S, Te) semiconductors using the CALPHAD method. The five-sublattice model has three additional sublattices to explicitly model interstitials, electrons, and holes. The experimental literature has been critically reviewed and many high temperature carrier concentration results used in previous assessments have been shown to be unreliable. First-principle calculations for the formation energies of neutral defects and their respective ionization energies have also been incorporated into the models. The models show an improvement over previous assessments of PbTe and are the first time PbS has not been treated as a stoichiometric compound in a CALPHAD assessment.